(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2026)
In developing nations where the urgent need for infrastructure and essential services has been historically neglected, public procurement often accounts for an average of around 30% of GDP highlighting the considerable reliance on public procurement to drive economic growth and improve public services in these regions. However, the large scale of public procurement makes it vulnerable to inefficiencies and corruption. Addressing these vulnerabilities is essential to ensure that public procurement can fulfill its critical role in driving national development. However, despite the pressing need for efficiency, public procurement processes in Kenya have been plagued by an inefficiency that manifests in the form of overpriced tendering processes, raising serious concerns about the integrity of public spending. Very few studies have examined the concept of public procurement overpricing in Kenya, and mechanisms to alleviate it. This study sought to examine the effect of: Procurement Planning; Procurement Audit; E-Supply Chain Management; and Procurement Risk Management; on Public Procurement Price Variance. The study collected data from 73 government agencies in Nairobi; and applied regression analysis to examine the statistical significance of the variables of study on Public Procurement Price Variance. The study established that public procurement management practices. However, the study also found gaps in procurement planning, lack of a concrete procurement audit framework, relatively low application of digitization, and relatively high usage of non-competitive methods of procurement. The study thus recommends for policy and research intervention into these public procurements practices-specifically, the perceived resistance to apply them.